Clinical Outcome of Eosinophilia in Patients with COVID-19: A Controlled Study : Eosinophilia and COVID -19 - Nair, Arun Prabhakaran; Soliman, Ashraf; Al Masalamani, Muna A.; De Sanctis, Vincenzo; Nashwan, Abdulqadir J.; Sasi, Sreethish; Ali, Elrazi A.; Hassan, Ola A.; Iqbal, Fatima M.; Yassin, Mohamed A. (Acta Biomedica Atenei Parmensis, 2020)
Background: Eosinophils can be considered as multifunctional leukocytes that contribute to various physiological and pathological processes depending on their location and activation status. There are emerging eosinophil-related considerations concerning COVID-19. Variable eosinophil counts have been reported during COVID-19. Whether these changes are related to the primary disease process or due to immunomodulation induced by the treatment has not yet been elucidated. Aim of the study: To describe changes in the differential leukocyte counts including eosinophils, in a cohort of symptomatic patients with confirmed COVID-19 and to correlate these changes, if any, with the severity of the disease. Patients and methods: We recorded the clinical data, lab findings, including inflammatory markers and leukocyte and differential count, course of the disease and severity score in 314 confirmed symptomatic cases of COVID-19. Results: Laboratory tests revealed that 28.7 % (n =86) had mild eosinophilia (eosinophil count > 500 <1,500/µL). Thirty-four patients (11.3%) had elevated absolute neutrophil count (ANC) (>8,000/µL), and 7 (2.3%) had decreased ANC (< 1,500/µl). Seven patients (2.3%) had lymphopenia (<1,000/µL) and 4 (4.67%) had lymphocytosis (> 4,000/µL). C-reactive protein (CRP) was elevated in 83 patients (27.6%). Chest X-Ray changes included: increased broncho vascular markings (38%), ground-glass opacity (GGO) pneumonitis (19.3%), lobar consolidation (5%), bronchopneumonia (8.3%), nodular opacity (1%), acute respiratory distress syndrome (ARDS) (2.3%), pleural effusion (1.0%) and other atypical findings (6.6%). Patients with eosinophilia had significantly lower CRP, and lower % of GGO, lobar and bronchopneumonia and ARDS in their chest images compared to patients without eosinophilia (p: <0.05). They also had a lower requirement for a hospital stay, ICU admission, mechanical ventilation, and oxygen supplementation versus patients without eosinophilia (p: <0.05). The eosinophils count was correlated negatively with the duration of ICU admission, mechanical ventilation, and oxygen supplementation and with CRP level (r: - 0.34, -0.32, -0.61 and - 0.39, respectively) (p: < 0.01).Conclusions: Our study reports a relatively high prevalence of eosinophilia in symptomatic COVID-19 positive patients. Patients with eosinophilia had a lower level of CRP, milder clinical course and better disease outcomes compared to those without eosinophilia. Our findings indicated a protective role of eosinophils in mitigating the severity of inflammatory diseases through an inhibitory mechanism, as evidenced by lower CRP. This protective role of eosinophils needs to be validated by further prospective studies.